P-MXene conductive ink and BC reinforced polymer composite film as well as preparation method and application thereof
By compounding p-MXene conductive ink with bacterial cellulose, and using aqueous polydopamine and aqueous polyurethane to form hydrogen bonds and π-π stacking, the problem of insufficient mechanical strength of MXene materials is solved, and the excellent mechanical and electrical properties of the composite film are achieved, and the electromagnetic shielding and stress-strain sensing functions are also provided.
Patent Information
- Application Number
- CN202510158023.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-13
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-02-13
AI Technical Summary
The insufficient mechanical strength of existing MXene materials leads to difficulties in practical applications, especially in the combination with bacterial cellulose, with few research.
By combining p-MXene conductive ink with bacterial cellulose (BC), the stable connection between MXene and bacterial cellulose is achieved by enhancing polymer complexing, and using aqueous polydopamine and aqueous polyurethane to form hydrogen bonds and π-π stacking.
The obtained composite film not only has excellent mechanical and electrical properties, but also has comprehensive properties such as electromagnetic shielding and stress and strain sensing, effectively improving the mechanical strength and stability of MXene materials.
Smart Images

Figure CN119613818A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of smart materials, and in particular to a p-MXene conductive ink and BC reinforced polymer composite film, and a preparation method and application thereof. Background Art
[0002] The new generation of bio-based functional composite materials has the advantages of light weight, high strength, high stability and rich functional active sites, which can meet the application requirements of high-performance enrichment recognition or wearable functional devices. Bacterial cellulose (BC) is a natural polymer generated by bacterial growth metabolism. It has the characteristics of low density, high tensile strength and elastic modulus, high specific surface area, multi-hydroxyl active interface and good biocompatibility. It is a widely studied structural substrate material. Compared with plant cellulose and other common materials, BC has the characteristics of high crystallinity, high water retention, high tensile strength and elastic modulus, and also has a typical three-dimensional network porous structure. Based on the special structural characteristics of BC and rich surface modification methods, it is particularly suitable for the composite construction of multi-level ordered structures at the micro-nano scale, further expanding its application in the field of flexible functional composite materials. Although BC still has problems such as low toughness, poor stability and insufficient mechanical properties, its excellent mechanical properties, biocompatibility, degradability and modifiability make BC hydrogel have immeasurable potential in the development of sensors.
[0003] MXene is a type of two-dimensional transition metal carbide and / or nitride with large specific surface area and metal-like conductivity, and is considered to be one of the potential candidate materials for wearable composite materials, and was confirmed to be a very promising electromagnetic shielding material in 2016. However, the mechanical strength of macroscopic materials prepared from pure MXene is insufficient, which leads to difficulties in practical application.
[0004] Currently, there are few studies on improving the mechanical strength of MXene by bacterial cellulose, which provides a new idea for solving the mechanical strength problem of MXene. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a p-MXene conductive ink and BC reinforced polymer composite film and a preparation method and application thereof. The composite film obtained by the present invention has excellent mechanical and electrical properties, and also has comprehensive properties such as electromagnetic shielding and stress strain sensing.
[0006] The present invention provides a p-MXene conductive ink and BC reinforced polymer composite film, wherein the composite film comprises MXene and bacterial cellulose, wherein the surface of the MXene is coated with water-based polydopamine, water-based polyurethane is embedded in the bacterial cellulose, and hydroxyl groups in the water-based polydopamine and amino groups in the water-based polyurethane form hydrogen bonds to connect the MXene and the bacterial cellulose.
[0007] Furthermore, the length of the bacterial fiber is not less than 20 μm, and the diameter is 50 nm-100 nm.
[0008] The present invention also provides a method for preparing the p-MXene conductive ink and BC enhanced polymer composite film, the preparation method comprising: Step S1: soaking bacterial cellulose in an aqueous polyurethane solution and drying at room temperature to obtain a bacterial cellulose / aqueous polyurethane nanocomposite material; Step S2: Dissolve lithium fluoride in hydrochloric acid solution, add titanium aluminum carbide (Ti 3 AlC 2 ), a first etching reaction, acid washing, solid-liquid separation, a second etching reaction, and obtaining an intermediate product; adding dopamine hydrochloride to a trishydroxyaminomethane solution (Tris), pre-reacting, adding a concentrated suspension of the intermediate product, reacting, solid-liquid separation, and retaining a precipitate; Step S3: The product obtained in step S2 is coated at least once on the surface of the bacterial cellulose / aqueous polyurethane nanocomposite material obtained in step S1, and dried at room temperature to obtain a p-MXene conductive ink and BC-reinforced polymer composite film.
[0009] Furthermore, in step S1, the soaking time is 1.5h-2.5h.
[0010] Furthermore, the mass concentration of the aqueous polyurethane solution is 5%-32%.
[0011] Furthermore, the method for preparing the aqueous polyurethane solution includes: dissolving and dispersing the aqueous polyurethane in deionized water.
[0012] Furthermore, in the present invention, as long as the bacterial cellulose is completely immersed in the aqueous polyurethane solution, the aqueous polyurethane can penetrate into the three-dimensional structure of the bacterial cellulose by controlling the mass concentration and immersion time of the aqueous polyurethane solution.
[0013] Furthermore, the room temperature drying temperature is 10°C-30°C.
[0014] Furthermore, the drying time at room temperature in step S1 is 46h-50h.
[0015] Furthermore, the drying time at room temperature in step S3 is 23h-25h.
[0016] Furthermore, the mass concentration of the lithium fluoride in the hydrochloric acid solution is 2 g / 40 mL.
[0017] Furthermore, the molar concentration of the hydrochloric acid solution is 9 mol / L.
[0018] Furthermore, the preparation method of the hydrochloric acid solution is: diluting the hydrochloric acid using deionized water to obtain it.
[0019] Furthermore, the mass concentration of the titanium aluminum carbide in the hydrochloric acid solution is 2 g / 40 mL.
[0020] Furthermore, the specific method of the first etching reaction is: stirring at 34° C.-36° C. for 23 h-25 h.
[0021] Furthermore, the specific method of washing the acid in step S2 is: washing with deionized water until the pH value of the product is close to 6, and then adding ethanol.
[0022] In the present invention, ethanol is added to further clean the acid wash. During the washing process using ethanol, ultrasonic treatment can also be performed simultaneously. It should be understood by those skilled in the art that ethanol is used for acid removal, and there is no particular restriction on the concentration of ethanol. Anhydrous ethanol or ethanol of other concentrations can be used. There is no restriction on the ultrasonic time, as long as the purpose of acid removal can be achieved. As an example, ethanol of the same volume as the hydrochloric acid solution can be added, and ultrasonic treatment is performed for 1 hour.
[0023] Furthermore, the specific method of the secondary etching reaction includes: adding deionized water to the precipitate after solid-liquid separation, centrifuging, and retaining the supernatant.
[0024] Furthermore, there is no special requirement for the amount of deionized water added during the secondary etching reaction, and it can be adjusted according to the retained supernatant, as long as the added deionized water can achieve secondary etching.
[0025] Furthermore, the specific parameters of the centrifugation are: centrifugation at 3900rpm-4100rpm for 2.5min-3.5min.
[0026] Furthermore, the mass concentration of dopamine hydrochloride in the trihydroxyaminomethane solution is 10 mg / 5 mL.
[0027] Furthermore, the pH value of the trishydroxyaminomethane solution is 8.4-8.6.
[0028] Furthermore, the pre-reaction time is 1.5h-2.5h.
[0029] Furthermore, the mass ratio of dopamine hydrochloride to the intermediate product is 2.5%-20%.
[0030] Furthermore, in step S2, the reaction time is 23h-25h, and stirring is performed during the reaction at a speed of 380rpm-420rpm.
[0031] Furthermore, the preparation method of the concentrated suspension of the intermediate product is as follows: after the secondary etching reaction, the supernatant is retained by centrifugation, and the retained supernatant is freeze-dried to obtain the concentrated suspension of the intermediate product.
[0032] Furthermore, the mass concentration of the concentrated suspension of the intermediate product is 2 mg / L.
[0033] The present invention also provides application of the p-MXene conductive ink and BC enhanced polymer composite film in a sensor.
[0034] The embodiments of the present invention have the following technical effects: 1. In the composite film obtained by the present invention, the waterborne polyurethane can fully penetrate into the three-dimensional structure of bacterial cellulose, and the elongation and toughness of the film are improved without destroying the original mechanical strength of the bacterial cellulose; and polydopamine can form a uniform coating layer on the surface of MXene, which physically prevents oxygen from directly contacting MXene, reduces the chance of oxygen molecules diffusing into the interior of the MXene layer, and thus slows down the occurrence of the oxidation reaction. In addition, polydopamine has a certain thickness and spatial structure, and can form an effective steric hindrance on the surface of MXene, making it difficult for oxygen to approach the active sites of MXene; the hydroxyl group (-OH) in polydopamine can not only react with the amino group (-NH 2 ) form hydrogen bonds; and π-π stacking occurs between the benzene rings in the waterborne polydopamine and the aromatic groups (such as benzene rings) in the waterborne polyurethane, thereby forming a stable supramolecular structure, thereby achieving the stability of the connection between bacterial cellulose and MXene, thereby improving the mechanical strength of the composite film and ensuring the stability of the composite film structure.
[0035] 2. In the present invention, in order to improve the mechanical strength of the composite film, bacterial cellulose, aqueous polydopamine and aqueous polyurethane with a length of not less than 20 μm are selected in the present invention. The longer bacterial cellulose not only has better mechanical strength, but also helps to ensure the structure of bacterial cellulose. The aqueous polyurethane can be fully embedded in the three-dimensional structure of bacterial cellulose, thereby helping to further improve the mechanical strength of bacterial cellulose; and the use of aqueous polydopamine and aqueous polyurethane can achieve self-assembly during the coating process, which is conducive to the formation of hydrogen bonds and π-π stacking, thereby improving the stability of the structure.
[0036] 3. In the present invention, the addition amount of aqueous polydopamine and aqueous polyurethane is further limited. When the concentrations of aqueous polydopamine and aqueous polyurethane are adjusted, firstly, the aqueous polydopamine can be controlled to be uniformly coated on the surface of MXene while reducing agglomeration; secondly, the number of hydrogen bonds that can be formed between aqueous polydopamine and aqueous polyurethane is controlled; and thirdly, the composite film is enabled to have better electrical and mechanical properties.
[0037] 4. The composite film obtained by the present invention has excellent mechanical and electrical properties, and also has comprehensive properties such as electromagnetic shielding and stress-strain sensing. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0039] Figure 1 This is a microscopic image of bacterial cellulose provided in Example 2 of the present invention.
[0040] Figure 2 This is a microscopic picture of the waterborne polyurethane embedded in bacterial cellulose according to Example 2 of the present invention.
[0041] Figure 3 This is a microscopic image of the composite film of Example 1.
[0042] Figure 4 It is the Fourier infrared spectrum of the comparative example.
[0043] Figure 5 It is the XRD diagram of Example and Comparative Example.
[0044] Figure 6 is the element distribution diagram of Example 1, wherein Figure 6 (a) is the distribution of each element in Example 1, Figure 6 (b) is the distribution of O element. Figure 6 (c) is the distribution of C element, Figure 6 (d) is the Ti element distribution.
[0045] Figure 7 This is a schematic diagram of the application of the p-MXene@WPU / BC composite film prepared in Example 5 in a stress sensor.
[0046] Figure 8 is the data collection after being applied to the sensor, where Figure 8 (a) is the relationship between the applied pressure and the ohmic resistance of the composite film. Figure 8 (b) is the RT curve during the compression-recovery cycle.
[0047] Fig. 9 The composite film prepared in Example 5 is applied to the data collection of the sensor, wherein Fig. 9 (a) is for fingers, Fig. 9 Middle (b) is for the wrist, Fig. 9 Middle (c) is for the elbow joint, Fig. 9 Middle (d) is for the face, Fig. 9 (e) is used to detect human motion.
[0048] Fig.10 It is the Fourier infrared spectrum of Example and Comparative Example. DETAILED DESCRIPTION
[0049] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0050] In the first aspect, some embodiments of the present invention provide a p-MXene conductive ink and BC reinforced polymer composite film, wherein the composite film comprises MXene and bacterial cellulose, wherein the surface of the MXene is coated with aqueous polydopamine, aqueous polyurethane is embedded in the bacterial cellulose, and the hydroxyl groups in the aqueous polydopamine and the amino groups in the aqueous polyurethane form hydrogen bonds to connect the MXene and the bacterial cellulose.
[0051] In some embodiments, the bacterial fiber has a length of not less than 20 μm and a diameter of 50 nm-100 nm.
[0052] In a second aspect, some embodiments of the present invention further provide a method for preparing the p-MXene conductive ink and BC reinforced polymer composite film, the preparation method comprising: Step S1: soaking bacterial cellulose in an aqueous polyurethane solution and drying at room temperature to obtain a bacterial cellulose / aqueous polyurethane nanocomposite material; Step S2: dissolving lithium fluoride in a hydrochloric acid solution, adding titanium aluminum carbide, performing a primary etching reaction, washing with acid, performing solid-liquid separation, performing a secondary etching reaction, and obtaining an intermediate product; adding dopamine hydrochloride to a trihydroxyaminomethane solution, performing a pre-reaction, adding a concentrated suspension of the intermediate product, reacting, performing solid-liquid separation, and retaining a precipitate; Step S3: The product obtained in step S2 is coated at least once on the surface of the bacterial cellulose / aqueous polyurethane nanocomposite material obtained in step S1, and dried at room temperature to obtain a p-MXene conductive ink and BC-reinforced polymer composite film.
[0053] In some embodiments, in step S1, the soaking time is 1.5h-2.5h.
[0054] In some embodiments, the mass concentration of the aqueous polyurethane solution is 5%-32%.
[0055] In some embodiments, the method for preparing the aqueous polyurethane solution includes: dissolving and dispersing the aqueous polyurethane in deionized water.
[0056] In some embodiments, the room temperature drying temperature is 10°C-30°C.
[0057] In some embodiments, the drying time at room temperature in step S1 is 46 hours to 50 hours.
[0058] In some embodiments, the drying time at room temperature in step S3 is 23h-25h.
[0059] In some embodiments, the mass concentration of lithium fluoride in the hydrochloric acid solution is 2 g / 40 mL.
[0060] In some embodiments, the molar concentration of the hydrochloric acid solution is 9 mol / L.
[0061] In some embodiments, the hydrochloric acid solution is prepared by diluting the hydrochloric acid using deionized water.
[0062] In some embodiments, the mass concentration of the titanium aluminum carbide in the hydrochloric acid solution is 2 g / 40 mL.
[0063] In some embodiments, the specific method of the etching reaction is: stirring at 34° C.-36° C. for 23 h-25 h.
[0064] In some embodiments, the specific method of washing the acid in step S2 is: washing with deionized water until the pH value of the product is close to 6, and then adding ethanol.
[0065] In some embodiments, the specific method of the secondary etching reaction includes: adding deionized water to the precipitate after solid-liquid separation, centrifuging, and retaining the supernatant.
[0066] In some embodiments, the specific parameters of the centrifugation are: centrifugation at 3900 rpm-4100 rpm for 2.5 min-3.5 min In some embodiments, the mass concentration of dopamine hydrochloride in the trishydroxyaminomethane solution is 10 mg / 5 mL.
[0067] Furthermore, the pH value of the trishydroxyaminomethane solution is 8.4-8.6.
[0068] In some embodiments, the pre-reaction time is 1.5h-2.5h.
[0069] In some embodiments, the mass ratio of dopamine hydrochloride to the intermediate product is 2.5%-20%.
[0070] In some embodiments, in step S2, the reaction time is 23h-25h, stirring is performed during the reaction, and the stirring speed is 380rpm-420rpm.
[0071] In a third aspect, some embodiments of the present invention also provide the application of the p-MXene conductive ink and BC-reinforced polymer composite film in sensors.
[0072] The following is described in conjunction with specific embodiments and comparative examples: Embodiment 1: (1) The purchased bacterial cellulose was taken out and soaked in a 0.1 mol / L sodium hydroxide solution and treated in a constant temperature water bath at 80°C for 12 hours to remove nutrients and live bacteria; after rinsing with deionized water to a pH of 7.0, a treated bacterial cellulose membrane was obtained; (2) Soaking the bacterial cellulose obtained in (1) in an aqueous polyurethane solution to obtain a WPU / BC film. The bacterial cellulose film was soaked in 50 mL of an aqueous polyurethane solution with a mass concentration of 32% for 2 hours to prepare a bacterial cellulose / polyurethane nanocomposite. Subsequently, the film was taken out of the dispersion and dried at room temperature (26°C) for 2 days to obtain a transparent nanocomposite film; (3) Ti 3 AlC 2 Powder (400 mesh) is used as the matrix, and MXene is prepared by LiF (lithium fluoride) / HCl (hydrochloric acid) solution etching method. Usually, 2g lithium fluoride is dissolved in 9M hydrochloric acid solution (40mL), stirred in a polytetrafluoroethylene container for 30 minutes, and 2g Ti is slowly added in an ice bath reaction container. 3 AlC 2The powder was stirred at 35 °C for 24 h, and washed repeatedly with deionized water (3500 rpm, 10 minutes) until the pH value was close to 6. 40 mL of ethanol was added, ultrasonicated for 1 h, and the precipitate was collected and centrifuged (10000 rpm, 10 minutes). Then 20 mL of deionized water was added to the precipitate and centrifuged at 4000 rpm for 3 min. The supernatant was retained, i.e., the MXene material. The MXene was freeze-dried to obtain a concentrated suspension of MXene. The mass concentration of the concentrated suspension of MXene was 2 mg / mL, and it was set aside.
[0073] (4) 10 mg of dopamine hydrochloride (DA) was added to 5 mL of trihydroxyaminomethane solution (pH ≈ 8.5) and pre-reacted for 2 h to reduce the amino content in the solution and avoid electrostatic flocculation after adding MXene. Then, 200 mL of concentrated MXene suspension was slowly added. The reaction lasted for 24 h under strong stirring at 400 rpm. After the reaction, the MXene suspension was centrifuged (3500 rpm, 5 min) and the precipitate was collected. According to the feed mass ratio of DA to MXene (2.5 wt%), the modified MXene was named p-MXene-2.5. Finally, the prepared p-MXene-2.5 was evenly coated on the WPU / BC film and dried at room temperature for 24 h. This process was repeated several times to obtain a composite film, which was recorded as: p-MXene-2.5@WPU / BC.
[0074] Embodiment 2: (1) Same as Example 1; (2) Same as Example 1; (3) Same as Example 1; (4) 10 mg of dopamine hydrochloride was added to 5 mL of trihydroxyaminomethane solution (pH ≈ 8.5) and pre-reacted for 2 h to reduce the amino content in the solution and avoid electrostatic flocculation after adding MXene, and then 100 mL of concentrated MXene suspension was slowly added. The reaction lasted for 24 h under strong stirring conditions. After the reaction, the MXene suspension was centrifuged (3500 rpm, 5 min) and the precipitate was collected and centrifuged. According to the feed mass ratio of DA to MXene (5 wt%), the modified MXene was named p-MXene-5. Finally, the prepared p-MXene-5 was evenly coated on the WPU / BC film and dried at room temperature for 24 h. This process was repeated several times to finally obtain a composite film, which was recorded as: p-MXene-5@WPU / BC.
[0075] Embodiment 3: (1) Same as Example 1; (2) Same as Example 1; (3) Same as Example 1; (4) Add 10 mg of dopamine hydrochloride to 5 mL of trihydroxyaminomethane solution (pH ≈ 8.5), pre-react for 2 h to reduce the amino content in the solution and avoid electrostatic flocculation after adding MXene, and then slowly add 50 mL of concentrated MXene suspension. Under strong stirring conditions, the reaction lasts for 24 h. After the reaction, the MXene suspension is centrifuged (3500 rpm, 5 min) and the precipitate is collected and centrifuged. According to the feed mass ratio of DA to MXene (10 wt%), the modified MXene is named p-MXene-10. Finally, the prepared p-MXene-10 is evenly coated on the WPU / BC film and dried at room temperature for 24 h. This process is repeated several times to finally obtain a composite film, which is recorded as: p-MXene 10 @WPU / BC.
[0076] Embodiment 4: (1) Same as Example 1; (2) Same as Example 1; (3) Same as Example 1; (4) 10 mg of dopamine hydrochloride was added to 5 mL of trihydroxyaminomethane solution (pH ≈ 8.5) and pre-reacted for 2 h to reduce the amino content in the solution and avoid electrostatic flocculation after adding MXene, and then 33 mL of concentrated MXene suspension was slowly added. The reaction lasted for 24 h under strong stirring conditions. After the reaction, the MXene suspension was centrifuged (3500 rpm, 5 min) and the precipitate was collected and centrifuged. According to the feed mass ratio of DA to MXene (15 wt%), the modified MXene was named p-MXene-15. Finally, the prepared p-MXene-15 was evenly coated on the WPU / BC film and dried at room temperature for 24 h. This process was repeated several times to finally obtain a composite film, which was recorded as: p-MXene-15@WPU / BC.
[0077] Embodiment 5: (1) Same as Example 1; (2) Same as Example 1; (3) Same as Example 1; (4) 10 mg of dopamine hydrochloride was added to 5 mL of trihydroxyaminomethane solution (pH ≈ 8.5) and pre-reacted for 2 h to reduce the amino content in the solution and avoid electrostatic flocculation after adding MXene, and then 25 mL of concentrated MXene suspension was slowly added. The reaction lasted for 24 h under strong stirring conditions. After the reaction, the MXene suspension was centrifuged (3500 rpm, 5 min) and the precipitate was collected and centrifuged. According to the feed mass ratio of DA to MXene (20 wt%), the modified MXene was named p-MXene-20. Finally, the prepared p-MXene-20 was evenly coated on the WPU / BC film and dried at room temperature for 24 h. This process was repeated several times to finally obtain a composite film, which was recorded as: p-MXene-20@WPU / BC.
[0078] Comparative Example 1: The purchased bacterial cellulose was taken out and soaked in a 0.1 mol / L NaOH solution and treated in a constant temperature water bath at 80°C for 12 hours to remove nutrients and live bacteria; after rinsing with deionized water to a pH of 7.0, a treated bacterial cellulose membrane was obtained, which was recorded as BC.
[0079] Comparative Example 2: (1) Same as Comparative Example 1; (2) The bacterial cellulose obtained in (1) was soaked in an aqueous polyurethane solution to obtain a WPU / BC film. The bacterial cellulose film was soaked in 50 mL of an aqueous polyurethane solution with a mass concentration of 5% for 2 hours to prepare a bacterial cellulose / polyurethane nanocomposite. Subsequently, the film was taken out from the dispersion and dried at room temperature (26°C) for 2 days to obtain a transparent nanocomposite film. The prepared nanocomposite was named BC / WPU5.
[0080] Comparative Example 3: (1) Same as Comparative Example 1; (2) The bacterial cellulose obtained in (1) was soaked in an aqueous polyurethane solution to obtain a WPU / BC film. The bacterial cellulose film was soaked in 50 mL of an aqueous polyurethane solution with a mass concentration of 7% for 2 hours to prepare a bacterial cellulose / polyurethane nanocomposite. Subsequently, the film was taken out from the dispersion and dried at room temperature (26°C) for 2 days to obtain a transparent nanocomposite film. The prepared nanocomposite was named BC / WPU7.
[0081] Comparative Example 4: (1) Same as Comparative Example 1; (2) The bacterial cellulose obtained in (1) was soaked in an aqueous polyurethane solution to obtain a WPU / BC film. The bacterial cellulose film was soaked in 50 mL of an aqueous polyurethane solution with a mass concentration of 9% for 2 hours to prepare a bacterial cellulose / polyurethane nanocomposite. Subsequently, the film was taken out from the dispersion and dried at room temperature (26°C) for 2 days to obtain a transparent nanocomposite film. The prepared nanocomposite was named BC / WPU9.
[0082] Comparative Example 5: (1) Same as Comparative Example 1; (2) The bacterial cellulose obtained in (1) was soaked in an aqueous polyurethane solution to obtain a WPU / BC film. The bacterial cellulose film was soaked in 50 mL of an aqueous polyurethane solution with a mass concentration of 12% for 2 hours to prepare a bacterial cellulose / polyurethane nanocomposite. Subsequently, the film was taken out from the dispersion and dried at room temperature (26°C) for 2 days to obtain a transparent nanocomposite film. The prepared nanocomposite was named BC / WPU12.
[0083] Comparative Example 6: (1) Same as Comparative Example 1; (2) The bacterial cellulose obtained in (1) was soaked in an aqueous polyurethane solution to obtain a WPU / BC film. The bacterial cellulose film was soaked in 50 mL of an aqueous polyurethane solution with a mass concentration of 32% for 2 hours to prepare a bacterial cellulose / polyurethane nanocomposite. Subsequently, the film was taken out from the dispersion and dried at room temperature (26°C) for 2 days to obtain a transparent nanocomposite film. The prepared nanocomposite was named 32% BC / WPU.
[0084] Comparative Example 7: Ti 3 AlC 2 Powder (400 mesh) was used as the matrix and LiF / HCl solution etching method was used to prepare MXene. Usually, 2 g of lithium fluoride was dissolved in 9 M hydrochloric acid solution (40 mL), stirred in a polytetrafluoroethylene container for 30 minutes, and 2 g of Ti was slowly added to the ice bath reaction container. 3 AlC 2 The powder was stirred at 35 °C for 24 h and washed repeatedly with deionized water (3500 rpm, 10 min) until the pH value was close to 6. 40 mL of ethanol was added, ultrasonicated for 1 h, centrifuged (10000 rpm, 10 min), the precipitate was collected and centrifuged, and then 20 mL of deionized water was added to the precipitate and centrifuged at 4000 rpm for 3 min to obtain MXene material.
[0085] Comparative Example 8: (1) Same as comparative example 7 (2) 10 mg of dopamine hydrochloride was added to 5 mL of trihydroxyaminomethane solution (pH ≈ 8.5) and pre-reacted for 2 h to reduce the amino content in the solution and avoid electrostatic flocculation after adding MXene, and then 50 mL of concentrated MXene suspension was slowly added. The reaction lasted for 24 h under strong stirring conditions. After the reaction, the MXene suspension was centrifuged (3500 rpm, 5 min) and the precipitate was collected and centrifuged. According to the feed mass ratio of DA to MXene (10 wt%), the modified MXene was named p-MXene-10.
[0086] Comparative Example 9: (1) The purchased bacterial cellulose was taken out and soaked in a 0.1 mol / L NaOH solution and treated in a constant temperature water bath at 80°C for 12 h to remove nutrients and live bacteria; after rinsing with deionized water to a pH of 7.0, a treated bacterial cellulose membrane was obtained; (2) Soaking the bacterial cellulose obtained in (1) in an aqueous polyurethane solution to obtain a WPU / BC film. The bacterial cellulose film was soaked in 50 mL of an aqueous polyurethane solution with a mass concentration of 32% for 2 hours to prepare a bacterial cellulose / polyurethane nanocomposite. Subsequently, the film was taken out of the dispersion and dried at room temperature (26°C) for 2 days to obtain a transparent nanocomposite film; (3) Ti 3 AlC 2 Powder (400 mesh) was used as the matrix and LiF / HCl solution etching method was used to prepare MXene. Usually, 2 g of lithium fluoride was dissolved in 9 M hydrochloric acid solution (40 mL), stirred in a polytetrafluoroethylene container for 30 minutes, and 2 g of Ti was slowly added to the ice bath reaction container. 3 AlC 2 The powder was stirred at 35 °C for 24 h, and washed repeatedly with deionized water (3500 rpm, 10 minutes) until the pH value was close to 6. 40 mL of ethanol was added, ultrasonicated for 1 h, centrifuged (10000 rpm, 10 minutes), and the precipitate was collected and centrifuged, and then 20 mL of deionized water was added to the precipitate and centrifuged at 4000 rpm for 3 min to obtain MXene material. The MXene was freeze-dried to obtain a concentrated suspension of MXene, and the mass concentration of the concentrated suspension of MXene was 2 mg / mL for standby use.
[0087] (4) The prepared MXene ink was evenly coated on the WPU / BC film and dried at room temperature for 24 h. This process was repeated several times to finally obtain a composite film, which was recorded as MXene@WPU / BC.
[0088] Comparative Example 10: BC was crushed and dissolved in deionized water to prepare a solution of about 2 mg / mL; it was mixed with aqueous polyurethane with a mass concentration of 32% in a volume ratio of 1:1, ultrasonicated (10 min), and vacuum filtered to prepare a WPU / BC film.
[0089] The embodiments and comparative examples of the present invention were tested: Mechanical property measurement: The composite films prepared in the examples and comparative examples were prepared into test samples (specifications: 100 mm×7 mm) according to the film strength test requirements, and strength tests were performed using a tensile strength measuring instrument (model: PT-990T).
[0090] Results and Analysis: Table 1 Mechanical properties test results of examples and comparative examples
[0091] Table 2 Electromagnetic shielding performance test results of the embodiments and comparative examples
[0092] In the composite film obtained by the present invention, bacterial cellulose is used to improve the mechanical properties of MXene materials. In the bacterial cellulose obtained by the present invention, water-based polyurethane is also embedded. The water-based polyurethane can fully penetrate into the three-dimensional structure of bacterial cellulose, and improve the elongation and toughness of the film without destroying the original mechanical strength of bacterial cellulose. It can be found from Comparative Examples 1 and Comparative Examples 2 to Comparative Examples 6 that the water-based polyurethane can further improve the mechanical strength of bacterial cellulose. In the present invention, the water-based polyurethane can not only fully penetrate into the three-dimensional structure of bacterial cellulose and improve the mechanical structure of bacterial cellulose, but also form hydrogen bonds with the water-based polydopamine on the surface of the MXene material, thereby facilitating the improvement of the MXene material by bacterial cellulose.
[0093] In terms of improving the mechanical strength of bacterial cellulose by water-based polyurethane, only when water-based polyurethane can stably penetrate into the three-dimensional structure of bacterial cellulose can the mechanical strength of bacterial cellulose be better optimized. Therefore, in the present invention, firstly, the length of bacterial cellulose is not less than 20 μm, which is conducive to ensuring the mechanical strength of bacterial cellulose itself and enabling water-based polyurethane to penetrate into the three-dimensional structure of bacterial cellulose. However, since the bacterial cellulose is broken up in Comparative Example 10, its mechanical properties are worse than those of Comparative Example 6. Secondly, in the present invention, water-based polyurethane must penetrate into the three-dimensional structure of bacterial cellulose to achieve the modification of bacterial cellulose. When the concentration of water-based polyurethane is low, the modification of bacterial cellulose is not significant. When the concentration of water-based polyurethane is high, the fluidity is poor and the penetration of water-based polyurethane is difficult. Therefore, in this case, the mass concentration of water-based polyurethane solution is further selected to be 5%-32%. By comparing Comparative Examples 2-6, it is further preferred that the mass concentration of water-based polyurethane solution is 32%.
[0094] The water-based polyurethane can also form hydrogen bonds with the water-based polydopamine on the surface of the MXene material, which is beneficial to the improvement of the MXene material by bacterial cellulose, which can be verified by comparing Comparative Example 9 with Examples 1 to 5.
[0095] On this basis, the mass concentration of aqueous polydopamine was further studied. When the mass concentration of aqueous polydopamine was low, the hydrogen bonds formed between aqueous polydopamine and aqueous polyurethane were less, while when the mass concentration of aqueous polydopamine was high, the aqueous polydopamine was agglomerated and could not be coated, thereby affecting the self-assembly of aqueous polydopamine and aqueous polyurethane, and finally causing the electrical and mechanical properties of the obtained composite film to decrease. Comparison and verification were performed through Examples 1 to 5 in Table 1.
[0096] Fig.10 It can be found that the formation of hydrogen bonds usually causes the stretching vibration absorption peak to move to a lower wave number (red shift) direction when comparing Comparative Example 9 with Example 3. This is because the formation of hydrogen bonds reduces the bond force constant between the hydrogen atom and the atom to which it is connected, thereby reducing the vibration frequency. Absorption peak intensity and width: The presence of hydrogen bonds can also increase the absorption intensity of certain vibration modes and broaden the absorption peak. These changes reflect the effect of hydrogen bonds on the vibration state of the molecule, as well as the strength and quantity of the hydrogen bonds themselves. It is further verified that the aqueous polydopamine and aqueous polyurethane in the present invention independently form hydrogen bonds.
[0097] In Table 2, by comparing Comparative Example 1 with Comparative Example 2, it is found that embedding waterborne polyurethane in bacterial cellulose can improve the electromagnetic shielding ability of bacterial cellulose. By comparing Examples 1 to 5, it is found that the addition of polydopamine can further improve the electromagnetic shielding effect of the composite film. However, with the addition of polydopamine, its electromagnetic shielding effect first increases and then decreases. The reason is that excessive addition of polydopamine causes MXene agglomeration, decreased conductivity, and reduced electromagnetic shielding performance. Therefore, it is further preferred that the mass ratio of dopamine hydrochloride to MXene is 2.5%-15%.
[0098] Figure 1 The bacterial cellulose obtained in Example 2 has a high-strength 3D interconnected network structure. Figure 2 It can be seen that the bacterial cellulose presents a typical compacted layered structure with a nanofiber conformation, which is due to the fact that a large amount of waterborne polyurethane in Example 2 is embedded in the bacterial cellulose and interacts with BC containing a large number of OH groups, thus realizing the self-assembly process of waterborne polydopamine and waterborne polyurethane. Figure 3 It shows that the p-MXene in Example 1 is evenly coated on the WPU / BC composite film, and the two are tightly combined.
[0099] Figure 4 The Fourier transform infrared spectrum shows that PDA successfully modifies MXene in Comparative Example 8, and p-MXene-10 shows the NH bending mode of aromatic secondary amines different from MXene in FT-IR spectrum (1460 cm -1 ) and CN stretching of the quinone ring (1250cm -1 ).exist Figure 5 In the X-ray diffraction (XRD) diagram, it can be seen that in Example 1, Ti 3 AlC 2 The enhancement characteristic peak of Ti 3 AlC 2 The Al layer peeling leads to the expansion of the interlayer spacing, proving that MXene has been successfully prepared. In addition, pure BC has two significant peaks at 15.4° and 35.2°, which are attributed to the (101) crystal plane and (002) crystal plane of typical cellulose, respectively. In the XRD spectrum, the WPU / BC composite film also shows the characteristic peaks of the (101) crystal plane and the (002) crystal plane of BC, indicating that BC and WPU are evenly mixed.
[0100] from Figure 6 It can be seen from the element analysis diagram that the elements in Example 1 are evenly distributed.
[0101] The p-MXene@WPU / BC composite film prepared in Example 5 was applied to the stress sensor. Conductive copper glue was pasted on both ends of the composite film, and copper wires were drawn out to serve as electrodes, which were respectively connected to the electrodes of a digital multimeter to collect electrical signals. Figure 7 The resistance changes under different pressures are recorded, and the results are shown in Figure 8 shown.
[0102] Figure 8 The slope of the curve in (a) increases and the resistance decreases, which corresponds well to the increase in applied pressure, showing a good ohmic contact and a stable linear relationship. Figure 8 In (b), during 550 compression-recovery cycles, the change in current is fast and stable, and the fluctuation of the RT curve is small and almost the same during the test. From the above experiments, it can be seen that the p-MXene@WPU / BC composite film has excellent stress sensing performance.
[0103] Preparation of a strain sensor: The composite film prepared in Example 5 is pasted with conductive glue on both sides, connected with wires, and connected to a digital multimeter to monitor the joint movements of the fingers, wrists and elbows. Fig. 9 shown.
[0104] in Fig. 9 (a)- Fig. 9 (c) The joint movements of the fingers, wrist and elbow joints, respectively. The composite film strain sensing material deforms, causing the resistance of the sensor to change. The relative resistance change value increases with the increase of the knee joint bending angle, indicating that the sensor can accurately measure joint movements at different angles and has good stability and repeatability. Fig. 9 (d) Speaking is the process of facial muscle changes that causes the sensor's resistance to change; Fig. 9 (e) The sensor can detect human body movement and has undergone 550 stretching and recovery cycles, which proves that the sensor of the present invention has good stability.
[0105] In summary, the composite film obtained by the present invention has excellent mechanical and electrical properties, and also has comprehensive properties such as electromagnetic shielding and stress-strain sensing.
[0106] It should be noted that the terms used in the present invention are only for describing specific embodiments, rather than limiting the scope of the present application. As shown in the present specification, unless the context clearly indicates an exception, the words "one", "a", "a kind of" and / or "the" do not specifically refer to the singular, but may also include the plural. The terms "include", "comprise" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method or device. In the absence of more restrictions, the elements defined by the sentence "include one..." do not exclude the presence of other identical elements in the process, method or device including the elements.
[0107] It should also be noted that the terms "center", "up", "down", "left", "right", "vertical", "horizontal", "inside", "outside", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. Unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", etc. should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be a connection between the two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0108] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the technical solutions of the embodiments of the present invention.
Claims
1. A p-MXene conductive ink and BC reinforced polymer composite film, characterized in that: The composite film comprises MXene and bacterial cellulose, wherein the surface of MXene is coated with water-based polydopamine, water-based polyurethane is embedded in the bacterial cellulose, and hydroxyl groups in the water-based polydopamine and amino groups in the water-based polyurethane form hydrogen bonds to connect MXene and bacterial cellulose.
2. The composite film according to claim 1, characterized in that The length of the bacterial fiber is not less than 20 μm, and the diameter is 50 nm-100 nm.
3. The method for preparing the p-MXene conductive ink and BC reinforced polymer composite film according to any one of claims 1 to 2, characterized in that: The preparation method comprises: Step S1: soaking bacterial cellulose in an aqueous polyurethane solution and drying at room temperature to obtain a bacterial cellulose / aqueous polyurethane nanocomposite material; Step S2: dissolving lithium fluoride in a hydrochloric acid solution, adding titanium aluminum carbide, performing a primary etching reaction, washing with acid, performing solid-liquid separation, performing a secondary etching reaction, and obtaining an intermediate product; adding dopamine hydrochloride to a trihydroxyaminomethane solution, performing a pre-reaction, adding a concentrated suspension of the intermediate product, reacting, performing solid-liquid separation, and retaining a precipitate; Step S3: The product obtained in step S2 is coated at least once on the surface of the bacterial cellulose / aqueous polyurethane nanocomposite material obtained in step S1, and dried at room temperature to obtain a p-MXene conductive ink and BC-reinforced polymer composite film.
4. The preparation method according to claim 3, characterized in that: In step S1, the soaking time is 1.5h-2.5h; The mass concentration of the aqueous polyurethane solution is 5%-32%.
5. The preparation method according to claim 3, characterized in that: The mass concentration of lithium fluoride in the hydrochloric acid solution is 2g / 40mL; The molar concentration of the hydrochloric acid solution is 9 mol / L; The mass concentration of the titanium aluminum carbide in the hydrochloric acid solution is 2 g / 40 mL.
6. The preparation method according to claim 3, characterized in that: The specific method of the first etching reaction is: stirring at 34° C.-36° C. for 23 h-25 h; The specific method of washing the acid in step S2 is: washing with deionized water until the pH value of the product is close to 6, and then adding ethanol; The specific method of the secondary etching reaction includes: adding deionized water to the precipitate after solid-liquid separation, centrifuging, and retaining the supernatant.
7. The preparation method according to claim 6, characterized in that: The specific parameters of the centrifugation are: centrifugation at 3900rpm-4100rpm for 2.5min-3.5min.
8. The preparation method according to claim 3, characterized in that: The mass concentration of dopamine hydrochloride in the trishydroxyaminomethane solution is 10 mg / 5 mL; The mass ratio of dopamine hydrochloride to the intermediate product is 2.5%-20%; The mass concentration of the concentrated suspension of the intermediate product is 2 mg / L.
9. The preparation method according to claim 3, characterized in that: The pre-reaction time is 1.5h-2.5h; In step S2, the reaction time is 23h-25h, and stirring is performed during the reaction at a speed of 380rpm-420rpm.
10. Use of the p-MXene conductive ink and BC-enhanced polymer composite film described in any one of claims 1 to 2 or the p-MXene conductive ink and BC-enhanced polymer composite film obtained by the preparation method of any one of claims 3 to 9 in a sensor.
Citation Information
Patent Citations
Waterborne polyurethane-MXene electromagnetic shielding bionic nanocomposite material film and preparation method
CN110698847A
MXene-based electromagnetic shielding film with porous foam structure and preparation method of MXene-based electromagnetic shielding film
CN113881105A
High-strength and high-toughness bacterial cellulose / polyurethane composites and their preparation and application
CN114933738A
Water-based MXene nanocellulose-based functional ink as well as preparation method and application method thereof
CN114958094A
Bacterial cellulose-polydopamine-MXene-coated AgNPs antibacterial hemostatic sponge as well as preparation method and application thereof
CN115944772A
Cited By
Modified MXene conductive polymer bacterial cellulose composite fiber electrode and preparation method and application thereof
CN120581544A